PENDEKATAN PERILAKU KEUANGAN TERHADAP KEPUTUSAN INVESTASI EMAS - Budiman, Johny; Ervina, Ervina (Profit: Jurnal Adminsitrasi Bisnis, 2020)
This research aims to analyze the influence of representativeness, overconfidence, anchoring, loss aversion, and regret aversion towards gold investment decision. Sample of this study are gold investors in Batam. Hypothesis test using multiple regression. Results from this research showed that investors used representativeness, overcinfidence, and loss aversion to determine their investment decision in gold. But anchoring and regret aversion factors have no significant impact in their investment decision. Further research for investment decision could be conducted in financial sector.